#
An electric current is flowing in a circular coil of radius a. at what distance from the centre of the axis of the coil will the magnetic field be 1/8th of its value at the centre.

1
by TianSalvi

Log in to add a comment

by TianSalvi

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

ΜThe point P is on the axis of the circular coil, I suppose. Let the center of the coil be O. Let OP be equal to x. Radius is a. Current is I. Let dL be a small element of the coil. So r = distance between dL and P = √(a²+x²).

Let the angle made by the line joining dL and P with the axis be θ. Here the angle θ is same for all elements on the coil. Also r is also same. The angle between the vectors dL and r is 90 deg. always. Let us say that the axis of the coil is x axis.

Cos θ = a / √(a² + x²) = a/r

Using Biot Savarts law:

The y and z components of the magnetic field induction By and Bz are zero, as the components along these axes will be cancelled by diametrically opposite elements.

B₀ at the center of the coil when x = 0, is: μ₀ I / (2 a)

Bx at a distance x on the axis will be B₀ / 8 when Cos θ = 1/2

ie., Cos² θ = 1/4 = a² / (a² + x²)

=> x² = 3 a²

=> x = √3 a

Let the angle made by the line joining dL and P with the axis be θ. Here the angle θ is same for all elements on the coil. Also r is also same. The angle between the vectors dL and r is 90 deg. always. Let us say that the axis of the coil is x axis.

Cos θ = a / √(a² + x²) = a/r

Using Biot Savarts law:

The y and z components of the magnetic field induction By and Bz are zero, as the components along these axes will be cancelled by diametrically opposite elements.

B₀ at the center of the coil when x = 0, is: μ₀ I / (2 a)

Bx at a distance x on the axis will be B₀ / 8 when Cos θ = 1/2

ie., Cos² θ = 1/4 = a² / (a² + x²)

=> x² = 3 a²

=> x = √3 a